PENGEMBANGAN PERANGKAT PEMBELAJARAN TEMATIK INTEGRATIF TEMA MENGHARGAI JASA PAHLAWAN BERBASIS SOSIOKULTURAL DI SEKOLAH DASAR - Waridah Waridah (JURNAL PENDIDIKAN DASAR, 2014)
Abstract: The aims of this research are to determine of learning equipment of thematic-integrative with socioculturalbasis suitable to students and determine the effectiveness of learning equipment of thematic-integrative with sociocultural basis in improving student learning outcomes elementary school. This research used the research and development. Development referred to the Borg and Gall development model which is classified into five stages consist of exploratory research, planning, product development, product testing, and finalization.Subjects of the research were fourth grade students of SD Negeri Serayu Yogyakarta at semester two in the academic year of 2013/2014 with the total number of students 72 which consist of 22 main test learners and 50 learners of field operational test.The results show thatresults of validation experts, practitioners, and colleagues demonstrated thematic-integrative learning equipment based sociocultural can be used with the excellent category. Effectiveness in terms of the results of post-test show an increase with an average of 36 % with a 84 % passing grade. There are significant differences in the effectiveness of the learning equipment between the experimental class and the control class with the significance p=0.001 ?0.05 .Key Words: thematic-integrative learning, learning equipment, sociocultural.Abstrak: Penelitian ini bertujuan untuk mengetahui perangkat pembelajaran tematik-integratif berbasis sosiokultural yang layak bagi peserta didik dan mengetahui efektivitas perangkat pembelajaran tematik-integratif berbasis sosiokultural dalam meningkatkan hasil belajar peserta didik SD. Jenis penelitian ini adalah penelitian dan pengembangan. Pengembangan dilakukan dengan mengacu pada model pengembangan Borg and Gall yang dikelompokkan ke dalam lima tahapan yaitu ekplorasi, perencanaan, pengembangan produk, uji produk dan finalisasi. Subjek uji coba penelitian adalah seluruh peserta didik kelas IV SD Negeri Serayu Yogyakarta pada semester kedua tahun ajaran 2013/2014 yang berjumlah 72 peserta didik terdiri dari 22 peserta didik uji utama dan 50 peserta didik uji coba terbatas. Hasil penelitian ini menunjukkan bahwa hasil validasi ahli, praktisi dan rekan sejawat menunjukkan perangkat pembelajaran tematik-integratif berbasis sosiokultural layak digunakan dengan kategori sangat baik. Keefektifan ditinjau dari hasil post-test menunjukkan ada peningkatan rata-rata 36% dengan ketuntasan belajar 84%. Ada perbedaan keefektifan perangkat pembelajaran yang signifikan antara kelas eksperimen dan kelas kontrol dengan signifikansi p=0,001?0,05.Kata Kunci: pembelajaran tematik-integratif, perangkat pembelajaran, sosiokultural.